AIEgens for biological process monitoring and disease theranostics. (November 2017) - Gu, Xinggui; Kwok, Ryan T.K.; Lam, Jacky W.Y.; Tang, Ben Zhong
Abstract: Biological processes are of great significance for the normal physiological functions of living organisms and closely related to the health. Monitoring of biological processes and diagnosis of diseases based on fluorescent techniques would provide comprehensive insight into mechanism of life and pathogenesis of diseases, precisely guiding therapeutic effect in theranostics. It largely relied on fluorophores with the properties of excellent photostability, large Stokes shift, high signal-to-noise ratio and free of aggregation-caused quenching (ACQ) effect. Luminogens with aggregation-induced emission characteristic (AIEgens) could serve as superior agents for biological process monitoring and disease theranostics. Herein, we review the recent results in the aspects of monitoring biological processes such as autophagy, mitophagy, mitochondrion-related dynamics, cell mitotic, long-term cellular tracing and apoptosis as well as the diagnosis of related diseases based on AIEgens in real time. As part of AIEgens and AIEgen-based nanoparticles with the functionalities of drugs, photosensitizers and adjuvants accompanied with imaging, they exhibit huge potential in theranostic systems for image-guided chemotherapy, photodynamic therapy, radiotherapy and so on. Collectively, these examples show the potentials of AIEgens for understanding disease pathogenesis, for drug development and evaluation, and for clinical disease diagnosis and therapy. Future research efforts focused on developing long-wavelength excitable and phosphorescence-emissive AIEgens with improved depth-penetration and minimized background interference for fluorescence and photoacoustic imaging, will extend the potential applications of AIEgens in in vivo .